Needs Analysis of Student Workshop Based on Discovery Learning on Static Fluid Materials In Palangka Raya - Ita Aulianingsih; Hadma Yuliani; Nur Inayah Syar (Universitas Pakuan, 2020)
Needs analysis is important before developing a product. The purpose of this research is to find out: 1). 11th grade physics material which is considered difficult by students 2). Teaching materials used in learning physics; 3). Knowing the need to develop student worksheets based on discovery learning This research is a quantitative descriptive study. The samples in this study were physics teachers and 11th grade students of Senior High School 10 Palangka Raya as many as 22 people. The results of this study are: 1). Physics material that is considered difficult by students is static fluid material with the percentage of students who choose this material is 77%. 2). The teaching materials used by teachers in physics subjects are modules, student worksheets and textbooks with the largest percentage selected being textbooks, which is 82%. 3). Students want student worksheets that have an attractive appearance, are easy to understand and lead to discovery learning, so as many as 100% feel the need to develop discovery learning-based student worksheets.